Distributed generation and cost efficiency of German electricity distribution network operators - Lisa Just; Heike Wetzel (Institute of Energy Economics at the University of Cologne (EWI), 2020)
In this paper, we use a comprehensive and unique data set of financial, technical and structural characteristics of German distribution network operators from 2011 to 2017 to estimate both the transient and persistent cost efficiency of German distribution network operators. In addition, we analyze the effect of an increasing capacity of distributed generation from renewable energy sources on the total costs of distribution network operators. Our results indicate an average cost reduction potential of approximately 12 percent in the short term and approximately 18 percent in the long term for German electricity distribution network operators. Furthermore, we find that distributed generation from renewable energy sources is a significant cost driver in the production process of network operators. Our study thus contributes to the ongoing debate on incentive regulation and efficiency benchmarking in electricity distribution industries and provides valuable insights for policymakers and regulators.
Keywords: L23; D24; L51; L94; 330; Electricity distribution; regulation; transient cost efficiency; persistent cost efficiency; distributed generation; stochastic frontier analysis